In vitro and in vivo study of primary epidermal allografts versus xenografts transplanted on full thickness wound in rabbits - Hanifi, Norlaily (2021)
Skin grafting has been evolving as an important application in reconstructive surgery. Skin grafting accelerates healing of wounds as well as reduces insensible fluid loss from burns and other wounds. It also reduces the formation of scars and accelerates cosmesis. Mixed reports on the survival of allogenic and xenogenic keratinocytes require further substantiation to determine their role in wound healing. The purpose of this study was to investigate the full thickness wound healing potential using primary epidermal allografts versus xenografts in rabbits. The rabbit and rat skins were harvested and cultured in vitro using specific growth media. Two full thickness wounds (2cm x 2cm) were created on the dorsum of the rabbits. Cultured epithelial allograft from the rabbits and xenograft from the rat were sprayed onto the freshly created wounds along with fibrin using the Tissomat device (Baxter, Austria). After four weeks, the rabbits were euthanized and skin biopsies were taken from each healed wound and subjected to histological evaluation using Haematoxylin and Eosin staining, immunohistochemical staining and also histochemical staining. The result from this study revealed that both graft showed favorable healing outcomes and healed without graft rejection. The scars that formed after the wound healed also desirable and healed with less scar formation. The immunological evaluation by flow cytometry analysis support the expected outcome of the study by showing there was no immunological rejection occurred. In conclusion, the primary epidermal allograft and xenograft have the potential to be used as askin substitute to replace skin defects. This can overcome the limitation of autologous skin donor site especially in burn cases.